2015
DOI: 10.1084/jem.20142284
|View full text |Cite
|
Sign up to set email alerts
|

Distinct germinal center selection at local sites shapes memory B cell response to viral escape

Abstract: Local germinal center reactions that persist in the lung after influenza infection are required for the generation of cross-reactive memory B cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(155 citation statements)
references
References 67 publications
(102 reference statements)
6
146
0
Order By: Relevance
“…Based on a previous observation in splenectomized immune thrombocytopenia patients that revealed the presence of persisting antigen-specific MBCs in the spleen (14, 51), we believe it is likely that this diverse pool of cells survives in tissues. Additionally, a recent study showed that tissue-resident MBCs in a mouse model are enriched for broadly neutralizing influenza-specific antibodies compared with those in circulation (52). If influenza vaccine responses in patients are originating from a diverse pool of tissue-resident MBCs, this mouse study could potentially explain how patients are able to mount a protective response to vaccination despite the low number of MBCs.…”
Section: Discussionmentioning
confidence: 95%
“…Based on a previous observation in splenectomized immune thrombocytopenia patients that revealed the presence of persisting antigen-specific MBCs in the spleen (14, 51), we believe it is likely that this diverse pool of cells survives in tissues. Additionally, a recent study showed that tissue-resident MBCs in a mouse model are enriched for broadly neutralizing influenza-specific antibodies compared with those in circulation (52). If influenza vaccine responses in patients are originating from a diverse pool of tissue-resident MBCs, this mouse study could potentially explain how patients are able to mount a protective response to vaccination despite the low number of MBCs.…”
Section: Discussionmentioning
confidence: 95%
“…De novo TLS formation in chronically inflamed tissues has been correlated with allograft rejection, autoimmune disease progression (9), and improved cancer outcomes (10). Influenza-induced TLS in the lung (but not nearby secondary lymphoid organs) and the subsequent generation of resident memory B cells were responsible for limiting virus escape after infection (11). In some tissues, in vivo TLS formation can be initiated by mature …”
Section: T Follicular Helper Cells (T Fh Cells) Are a Functionally DImentioning
confidence: 99%
“…Therefore, by using fluorescent HA probes, we first sought to trace virus-specific memory B cell responses after s.c. vaccination as previously reported ( Fig. 1) (23,24). We selected whole-virion vaccines of the H5N1 subtype for this study, because this is the only whole-virion vaccine currently stockpiled in Japan for humans.…”
Section: Alum-adjuvanted Whole-and Split-virion Vaccines Comparably Imentioning
confidence: 99%